Flexible production concept for the automotive industry - Almedal, Ludwig; Ivarsson, Oscar (My University, 2023)
Aurobay is an automotive powertrain supplier and originates from Volvo Car Cooperation. The company have productions sites in Skövde, Sweden, and in Zhangjiakou, China. Today automotive industry is in a redefine phase with new emission legislature and new technologies requiring automotive manufactures to be fast in order to adapt. One way is by being flexible. The project team has, with the DMAIC methodology, examined several low volume flexible production concepts for manufacturing of cylinder heads (CH), cylinder blocks (CB) and mass balancing system (MBS). When defining the project scope. Did the project team learn that the question “what is flexibility?” and “what is prioritised in flexible production concept?” needed to be addressed. During the define phase, voice of the customer disclosed the need of a new ways of machining the products as well as new perspectives and approaches. Boundaries of were identified accordingly as volume of ranging between10 000 to 30 000 units, no R&D, i.e., product development, and the product range consist of VEP and VED CB and CH generation 1 and 3 plus MBS. In the measure (M) phase was the qualitative tool interviews used to collect data about flexibility but also validated with agreement analysis and hypothesis testing. The output displayed that the assembly department had a common picture of flexibility and what to prioritise to succeed meanwhile support function and the machining department had a more various picture. Conclusions drawn from simulated the concept was that utilisation rate is low and lot of non-value adding time. This is mainly caused by high set-up time, the complexity in job-shop and met the demand of flexibility. By removing variants ZPI could not handle can the production be a more standardise process and set up time decrease to less than 35% of working time. The edge of knowledge is moved forward but to implement flexible concept is future research concerning standardisation and multifunctional tools needed to meet the demand of tomorrow.
Keywords: Flexibility; machining; standardisation; system; production concept.